Assumptions and problems with Fe-Mg garnet - biotite diffusion based petrological cooling rates: a case study in granulites and migmatites fromcentral Ribeira Fold Belt, SE Brazil - Santos,T. M. Bento dos (2009)
The São Fidelis - Santo António de Pádua sector of central Ribeira Fold Belt is mainly composed of migmatites, granulites and blastomylonites. Application of two contrasting methodologies to obtain petrological cooling rates based on Fe-Mg diffusion between garnet and respective biotite inclusions proved unfruitful. This was mainly due to: a) high dispersion of results caused by open-system behaviour; and b) narrow closure temperature variation caused by garnet reequilibration at high temperatures followed by very fast cooling. The obtained results are mainly qualitative but in broad agreement with previously obtained thermochronological results based on integration of multiple isotopic systems.